Back Cover: Organomagnesium‐Catalyzed Isomerization of Terminal Alkynes to Allenes and Internal Alkynes (Chem. Eur. J. 22/2015). Issue 22 (26th May 2015) - Rochat, Raphaël; Yamamoto, Koji; Lopez, Michael J.; Nagae, Haruki; Tsurugi, Hayato; Mashima, Kazushi
<x xml:space="preserve">Abstract</x> In a first step, organomagnesium catalysts completely transform terminal alkynes into allenes before these are further converted to the final products, internal alkynes, in a second step, allowing for isolation of the intermediate allenes. This is illustrated by three water tanks, symbolizing the substrate, the intermediate product, and the final product, which are connected by tubes that are regulated by linked magnesium stopcocks, allowing only one transformation at a time. For more details, see the Full Paper by H. Tsurugi, K. Mashima, and co‐workers on page 8112 ff.